Стихотворения, 1979-1987 - Друнина Юлия Владимировна (1989)
Экземпляры: Селтинская районная библиотека (аб) (20200317) / Инвентарный номер: 147891 / Цена: / Авт.знак: Д 76 / ГРНТИ: 17.82.10 / ББК: 84(2=411.2)6